EFEKTIVITAS HUKUM CAMBUK DALAM MENGURANGI KASUS KHALWAT PADA MAHKAMAH SYARIAH LHOKSUKON - Muhammad Jafar; Fohan Muzakir (Jurnal Syariah dan Ekonomi Islam, 2023)
This research aims to analyze the effectiveness of flogging laws in reducing khalwat cases at the Lhoksukon Syariah Court. The research was conducted using descriptive qualitative methods, using observation methods and conducting interviews. The results of the research show that the implementation of caning is a form of punishment applied by the Lhoksukon Syariah Court to reduce the special nature of Khalwat. The caning punishment applied is in accordance with Qanun number 14 of 2003 concerning khalwat. In the implementation of Islamic law, the issue of khalwat is regulated by Qanun Number 14 of 2003, the formation of this qanun is a form of concern for the Aceh government, especially North Aceh Regency, towards "decency" rules or regulations concerning the act of adultery, the qanun which regulates the offense of khalwat In principle, it is an effort to prevent cases of adultery from developing in the North Aceh Regency area. In Islamic legal terms, preventive measures like this are called sadd al-dzari'ah (closing the road). Namely closing the road so that cases of adultery do not occur.